Anywhere But Here : Black Intellectuals in the Atlantic World and Beyond - Werner, Anja; Scott, Jennifer, 1967-; Radcliffe, Kendahl (Book collections on Project MUSE., 2015)
"Anywhere But Here brings together new scholarship on the cross-cultural experiences of intellectuals of African descent since the eighteenth century. The book embraces historian Paul Gilroy's prominent thesis in The Black Atlantic and posits arguments beyond The Black Atlantic's traditional organization and symbolism. These essays expand categories and suggest patterns that have united individuals and communities across the African diaspora. They highlight the stories of people who, from their intercultural and often marginalized positions, challenged the status quo, created international alliances, cultivated expertise and cultural fluency abroad, as well as crafted physical and intellectual spaces for their self-expression and dignity to thrive. What, for example, connects the eighteenth-century Igbo author Olaudah Equiano with 1940s literary figure Richard Wright; nineteenth-century expatriate anthropologist Antenor Fermin with 1960s Haitian emigres to the Congo; Japanese Pan-Asianists and Southern Hemisphere Aboriginal activists with Jamaican-born Marcus Garvey; or Angela Davis with artists of the British Black Arts Movement, Ingrid Pollard and Zarina Bhimji? They are all part of a mapping the reaches across and beyond the boundaries typically associated with the 'Black Atlantic'"--